(untitled) (Pedagogy of Higher and Secondary Education, 2009)
This article includes the information about the problem of formation of abilities of the educational activity, nhich regpand to schadchildren’s age - ulated development. It is uncovered the essence of the concept which the ubilitier and habits are famed in junior schoolchildren.